1997
DOI: 10.1021/tx9700230
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Metabolism of N-(5-Chloro-2-methylphenyl)-N‘-(2-methylpropyl)thiourea:  Species Comparison and Identification of a Novel Thiocarbamide−Glutathione Adduct

Abstract: The in vitro metabolism of SDZ HDL 376, a thiocarbamide developed for the treatment of atherosclerosis, was investigated in rat, dog, monkey, and human liver microsomes, as well as in rat and human liver slices. [14C]SDZ HDL 376 was extensively metabolized in all the species except human. In rat liver microsomes an S-oxide was the major metabolite. In human and monkey microsomes, carbon hydroxylation was favored. The NADPH-dependent oxidation of SDZ HDL 376 resulted in covalent binding to microsomal protein. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…The oxidative desulfuration of the thiourea structural moiety (R-NH-C(0S)-NR 2 ) leading to the formation of a formamidine structure (i.e., R-N0CH-NR 2 ) is a well-known process already described by Walter et al [30]. It occurs both upon hydrogen peroxide treatment [30] or enzymatically [31].…”
Section: Resultsmentioning
confidence: 99%
“…The oxidative desulfuration of the thiourea structural moiety (R-NH-C(0S)-NR 2 ) leading to the formation of a formamidine structure (i.e., R-N0CH-NR 2 ) is a well-known process already described by Walter et al [30]. It occurs both upon hydrogen peroxide treatment [30] or enzymatically [31].…”
Section: Resultsmentioning
confidence: 99%
“…It has long been known that in vivo ETA demonstrates more consistent antitubercular activity than one would expect from in vitro examination of its minimal inhibitory concentration (MIC), and it has been demonstrated that a major metabolite of ETA in vivo is its S-oxide (2), which shows comparable in vitro activity (18)(19)(20)(21)(22). A wide variety of toxic thiocarbonyl-containing compounds have been shown to be converted to the corresponding S-oxides during in vivo metabolism by mammals supporting this as an intermediate oxidation in the metabolic activation of ETA (23).…”
mentioning
confidence: 99%
“…A wide variety of toxic thiocarbonyl-containing compounds have been shown to be converted to the corresponding S-oxides during in vivo metabolism by mammals supporting this intermediate oxidation in the metabolic activation of ETH [43]. .…”
Section: Eth Metabolitesmentioning
confidence: 95%